Auctioning public assets : analysis and alternatives - Janssen, Maarten Christiaan Wilhelmus, 1962- (Cambridge University Press, 2004)
This book provides an overview of the economic issues that are involved in the privatisation of firms, previously under public control. Combining a theoretical framework with case studies it asks which allocation mechanism can a government adopt and how will the choice of allocation mechanism affect future market outcomes?